Nasopharyngeal teratoma ('hairy polyp'), Dandy-Walker malformation, diaphragmatic hernia, and other anomalies in a female infant. Issue 12 (December 1990) - Aughton, D J; Sloan, C T; Milad, M P; Huang, T E; Michael, C; Harper, C
Abstract : Nasopharyngeal teratomas are rare and are infrequently associated with extra-oral malformations. The case of a premature female infant with multiple congenital anomalies, including nasopharyngeal teratoma, Dandy-Walker malformation, diaphragmatic hernia, and congenital heart defect, is presented. This constellation of malformations does not appear to have been reported previously.